Leading with spirit, presence, and authenticity - Kathryn Goldman Schuyler (Jossey-Bass, 2014)
Leading with Spirit, Presence, and Authenticity presents the perspectives of leaders, social scientists, and educators from around the world on the topic of developing inner wisdom. Structured around the notions of spirit, presence, and authenticity, the book encourages readers to reflect on their own lives as they read about their colleagues' diverse experiences, all in an effort to address difficult global systems challenges with a foundation of various wisdom lineages and practices